Correlation between Theory of Planned Behavior and Smoking Cessation: A Meta-Analysis - Mitha Amelia Rahmawati; Bhisma Murti; Hanung Prasetya (Journal of Health Promotion and Behavior, 2022)
Background: The increasing consumption of cigarettes that continues to occur among the community has an impact on the higher rates of morbidity and mortality. Active smokers who have a tendency to quit smoking can be identified by measuring their intentions. The theory of planned behavior is a concept that influences the study of an individual's behavior. This study aims to estimate the magnitude of attitudes towards behavior, subjective norms, and perceptions of behavioral control with behavior to stop smoking.Subjects and Method: This study is a systematic review and meta-analysis with the acronym PICO, namely population: smokers. Intervention: positive attitude toward behavior, supportive subjective norm, strong perception of behavioral control. Comparison: attitude towards negative behavior, subjective norms do not support, perception of behavior control is weak. Outcome: smoking cessation behavior. Data collection was obtained from 4 databases, namely: Google Scholar, PubMed, Science Direct and ProQuest with the keywords used "attitude toward behavior" AND "subjective norm" AND "perceived behavior control" AND "quit smoking" OR "quit smoke" OR "smoking cessation". The inclusion criteria used were full English paper with cross sectional design in 2012-2022. The analysis of this study used RevMan 5.3 software.            Results: A total of 7 articles originating from the Asian and American continents were included in this study. Based on the results of the analysis of smokers who had positive behavior (aOR = 2.77; 95% CI = 1.06 to 1.37; p <0.001), subjective norms were supportive (aOR = 1.08; 95% CI = 0.98 to 1.18; p <0.001), as well as perceived control behavioral (aOR = 1.19; 95% CI = 1.00 to 1.42; p < 0.001) were more likely to quit smoking compared to smokers who had negative behavior, unsupportive subjective norms, and weak perceptions of behavioral control.Conclusion: Positive behavior, supportive subjective norms, perception of strong behavioral control increase the likelihood of smoking cessation in active smokers.Keywords: theory of planned behavior, stop smoking, adjusted odds ratio.Correspondence:Mitha Amelia Rahmawati. Masters Program in Public Health, Universitas Sebelas Maret. Jalan Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: mithaamelia1909@gmail.com. Mobile: +6285853723823.Journal of Health Promotion and Behavior (2022), 07(04): 299-312DOI: https://doi.org/10.26911/thejhpb.2022.07.04.03